Mining Educational Data for Predicting Higher Secondary School Student’s Grade Using ID3 Algorithm (International Journal of Engineering and Computer Science, 2015)
Educational data mining concerns with developing methods for discovering knowledge from data that come from educational domain. The performance in higher secondary school education in India is a turning point in the academic lives of all students. It is essential to develop predictive data mining model for student’s performance so as to identify the slow learners and make necessary steps for the improvement of the students. In this paper, a new system that will predict students’ higher secondary grades based on academic and personal details of the students. ID3 decision tree algorithm was used to train the data of the school students sets. The knowledge represented by decision trees were extracted and presented in the form of IF-THEN rules. A set if prediction rules were extracted from id3 decision tree algorithm and the efficiency of the generated model was found.